Analysis of Social Media and Ubiquitous Data International Workshops MSM 2010, Toronto, Canada, June 13, 2010, and MUSE 2010, Barcelona, Spain, September 20, 2010, Revised Selected Papers - Atzmueller, Martin; Hotho, Andreas; Strohmaier, Markus; Chin, Alvin (Lecture Notes in Artificial Intelligence, 2011)
This book constitutes the joint thoroughly refereed post-proceedings of The Modeling Social Media Workshop, MSM 2010 held in Toronto, Canada in June 2010 and the International Workshop on Mining Ubiquitous and Social Environments, MUSE 2010, held in Barcelona, Spain in September 2010. The eight revised full papers included were carefully reviewed and selected after two rounds of reviewing and revision. The papers address various aspects of the analysis and engineering of socio-computational systems in which social, ubiquitous and computational processes are interdependent and tightly interwoven.